Experiencias extraescolares en relación con la educación cultural y artística de los niños de tres a cuatro años del Centro Educativo Pequeños Creadores (2019)
This degree work is focused to analyze the conditions that are created in the cultural and artistic education environment of children studying in Centro Educativo Pequeños Creadores with ages of three and four years old regard to activities and experiences that these children develop in their extracurricular time, a theoretical and conceptual tracking have been made that allowed the investigation to have a solid foundation to its develop, among the authors consulted can be mentioned Ministerio de Educación Nacional de Colombia, Lev Vygotsky, Ministerio de Cultura de Colombia, among others. The degree work was addressed from an established methodology, with a qualitative approach, supported by a hermeneutical method, using cartography as a strategy, which was successful in collecting data thanks to techniques such as participant observation and the questionnaire.